Roles of AIM2 Gene and AIM2 Inflammasome in the Pathogenesis and Treatment of Psoriasis - Wang, Jieyi; Gao, Jing; Huang, Cong; Jeong, Sohyun; Ko, Randy; Shen, Xue; Chen, Chaofeng; Zhong, Weilong; Zou, Yanfen; Yu, Bo; Shen, Changbing (Frontiers in Genetics, 2022)
Psoriasis is an immune-mediated chronic inflammatory skin disease caused by a combination of environmental incentives, polygenic genetic control, and immune regulation. The inflammation-related gene absent in melanoma 2 (AIM2) was identified as a susceptibility gene for psoriasis. AIM2 inflammasome formed from the combination of AIM2, PYD-linked apoptosis-associated speck-like protein (ASC) and Caspase-1 promotes the maturation and release of inflammatory cytokines such as IL-1β and IL-18, and triggers an inflammatory response. Studies showed the genetic and epigenetic associations between AIM2 gene and psoriasis. AIM2 gene has an essential role in the occurrence and development of psoriasis, and the inhibitors of AIM2 inflammasome will be new therapeutic targets for psoriasis. In this review, we summarized the roles of the AIM2 gene and AIM2 inflammasome in pathogenesis and treatment of psoriasis, hopefully providing a better understanding and new insight into the roles of AIM2 gene and AIM2 inflammasome in psoriasis.